On the people's terms : a republican theory and model of democracy - Pettit, Philip, 1945- (John Robert Seeley lectures., 2012)
"According to republican political theory, choosing freely requires being able to make the choice without subjection to another and freedom as a person requires being publicly protected against subjection in the exercise of basic liberties. But there is no public protection without a coercive state. And doesn't state coercion necessarily take from the freedom of the coerced? Philip Pettit addresses this question from a civic republican perspective, arguing that state interference does not involve subjection or domination if there is equally shared, popular control over government"--